Effects of Stem Cuttings and Growing Media on Vegetative Growth of Cassava (Manihot esculenta Crantz) - Fadilah, Lya Nailatul; Gustiar, Fitra; Sefrila, Marlin; Widjajanto, Didik Wisnu; Ria, Rofiqoh Purnama; Rahmah, Adiba Mutia (Agro Bali : Agricultural Journal, 2026)
Cassava (Manihot esculenta Crantz) leaves are widely utilized as a leafy vegetable due to their high protein and bioactive compound content. However, information regarding suitable planting materials and planting media composition for optimizing cassava leaf production is still limited. This study aimed to determine the appropriate planting material and planting media composition to improve the growth and yield of cassava leaf shoots. The experiment was conducted from July-August 2024 at the Experimental Field, Faculty of Agriculture, Universitas Sriwijaya. This study used a factorial Randomized Block Design consisting of two factors: planting material (three levels: upper stem, middle stem, and lower stem) and planting media composition (three levels: soil, soil + cattle manure, and soil + goat manure). Each treatment combination was replicated 3 times, and each experimental unit consisted of 3 plants, resulting in 9 treatment combinations × 3 replications × 3 plants per unit, for a total of 81 plants in the experiment. The results showed that the use of middle-stem cuttings combined with soil + cattle manure resulted in higher sprout growth, number of leaves, SPAD index, and leaf-shoot harvest compared to other treatments. Regular leaf shoot pruning increases the number of edible leaf shoots. The selection of planting material with the right composition of planting medium can sustainably increase the productivity of leafy vegetables in cassava.